2019
DOI: 10.1177/1742715019827405
|View full text |Cite
|
Sign up to set email alerts
|

Shades of grey in implicit effective leadership: Searching for clarity in the midst of paradox

Abstract: In this paper, we extend research on implicit leadership theories by exploring and clarifying the content and structure of effective leader prototypes. We invited 78 Chinese and 50 American business practitioners to describe effective and ineffective leaders. Drawing on grounded theory approaches, we coded 671 statements of participants and found 41 leader attributes. After grouping these attributes into eight themes, we found that the structure and content of effective and ineffective leader prototypes indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(175 reference statements)
2
6
0
Order By: Relevance
“…Their effective leader themes were "competent, distinguished, dynamic, helpful, social-skilled, and ethical and the ineffective ones were destructive and powerful". Jiang et al's (2019) competent and social-skilled themes were quite similar to our relationship-oriented theme while their distinguished and dynamic themes resemble our task-oriented theme. Their dynamic theme corresponds to our change-oriented theme.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 60%
See 3 more Smart Citations
“…Their effective leader themes were "competent, distinguished, dynamic, helpful, social-skilled, and ethical and the ineffective ones were destructive and powerful". Jiang et al's (2019) competent and social-skilled themes were quite similar to our relationship-oriented theme while their distinguished and dynamic themes resemble our task-oriented theme. Their dynamic theme corresponds to our change-oriented theme.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 60%
“…Most of the attributes in this study were also mentioned in other studies. For example, intelligent and charismatic attributes in the present study were found in Epitropaki & Martin (2004), Jiang et al (2019), Lord et al (1984), Offerman et al (1994, and sincere, knowledgeable, and experienced were identified in Offerman et al (1994), Martin (2004), andJiang et al (2019). The goal-oriented theme was obtained in Lord et al (1984), Offerman et al (1994), and Jiang et al (2019.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 55%
See 2 more Smart Citations
“…An essential aspect of this respect is the employee's stage of development because employees in the early stages of development who have relatively little competence or experience usually need clear direction to maintain high-performance levels (Hersey and Blanchard, 1977). Dominant leaders (and such leaders are expected in the uniformed services, among others) may stifle employees' initiative and creativity by being inflexible in their behavior, which is why it is so essential to understand their expectations and needs and therefore to recognize the generational diversity of generations, cultural diversity is also essential (Jiang et al, 2019). This is also confirmed by Schyns and Schilling, who, in their research, indicated that employees might have different perceptions of leaders' effectiveness in terms of objective organizational performance compared to their subjective job satisfaction (Schyns and Schilling, 2011).…”
Section: The Challenge Of the Leader -Building Engagement Across Generational Diversitymentioning
confidence: 99%